Linking Capacity Development to GOOS Monitoring Networks to Achieve Sustained Ocean Observation - Bax, Nicholas J.; Appeltans, Ward; Brainard, Russell; Duffy, J. Emmett; Dunstan, Piers; Hanich, Quentin; Harden Davies, Harriet; Hills, Jeremy; Miloslavich, Patricia; Muller-Karger, Frank Edgar; Simmons, Samantha; Aburto-Oropeza, O.; et al. (Frontiers in Marine Science, 2018)
Developing enduring capacity to monitor ocean life requires investing in people and their institutions to build infrastructure, ownership, and long-term support networks. International initiatives can enhance access to scientific data, tools and methodologies, and develop local expertise to use them, but without ongoing engagement may fail to have lasting benefit. Linking capacity development and technology transfer to sustained ocean monitoring is a win-win proposition. Trained local experts will benefit from joining global communities of experts who are building the comprehensive Global Ocean Observing System (GOOS). This two-way exchange will benefit scientists and policy makers in developing and developed countries. The first step toward the GOOS is complete: identification of an initial set of biological Essential Ocean Variables (EOVs) that incorporate the GEO Essential Biological Variables (EBVs), and link to the physical and biogeochemical EOVs. EOVs provide a globally consistent approach to monitoring where the costs of monitoring oceans can be shared and where capacity and expertise can be transferred globally. Integrating monitoring with existing international reporting and policy development connects ocean observations with agreements underlying many countries’ commitments and obligations, including under SDG 14, thus catalysing progress towards sustained use of the ocean. Combining scientific expertise with international capacity development initiatives can help meet the need of developing countries to engage in the agreed UN initiatives including new negotiations for management of Biodiversity Beyond National Jurisdiction, and the needs of the global community to understand how the ocean is changing.